Prix Meret Oppenheim 2010 : Interviews. - Münch, Andreas; Huser, Ursula (Bern : Bundesamt für Kultur, 2010)
Sollfrank, Cornelia ; Beckel, Inge ; Müller, Claudia ; Müller, Julia ; Duyvendak, Yan ; Badrutt, Ursula
boek